2013
DOI: 10.4103/0971-5851.125245
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and expected outcome of acute lymphoblastic leukemia in children and adolescents: An experience from Eastern India

Abstract: Objective:Research in Eastern India especially among children and adolescents for acute lymphoblastic leukemia (ALL) have not been well documented until recently when it was conducted at a cancer institute of tertiary care with primary objectives of examining and correlating different cell surface markers involved with respect to disease surveillance thereby highlighting it as a strong prognostic marker for future diagnosis and treatment.Materials and Methods:A total of 500 consecutively selected ALL patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…Similar study was observed in the West, the predominant immunophenotype observed in ALL was B-ALL, accounting for 60-80% of total cases, whereas T-ALL comprised only of 15-20% [9]. In one study from eastern India, both T-ALL (50.4%) and B-ALL (49.6%) incidence was almost equal in distribution [10].…”
Section: Discussionsupporting
confidence: 59%
“…Similar study was observed in the West, the predominant immunophenotype observed in ALL was B-ALL, accounting for 60-80% of total cases, whereas T-ALL comprised only of 15-20% [9]. In one study from eastern India, both T-ALL (50.4%) and B-ALL (49.6%) incidence was almost equal in distribution [10].…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, there is paucity of data addressing clinical features, prognostic parameters and outcome of T ALL in developing countries like India, where this ALL subtype is more frequently observed than in the developed nations (16,17) . Disease free survival and event free survival were higher in B ALL in adolescent patients as compared to T ALL who had significantly low survival rates (18) . Hence even though the present study showed the predominant type to be B ALL (85.6%) we concentrated on T ALL which constituted only 14.4%.CD34 is a human stage specific haematopoetic differentiation antigen and is expressed in early undifferentiated haematopoetic stem cells,both in lymphoid and myeloid lineage.In leukemic cells it remains to be expressed over several stages of lymphoid and myeloid maturation.The incidence of CD34 positvity is low in T ALL worldwide (7)(8)(9)(10)(11) (table.2) which is in contrast to the present study.…”
Section: Discussionmentioning
confidence: 82%
“…[17] Another recent Eastern Indian study reported 50.4% incidence of T-cell immunophenotype. [8] Western studies have reported <10% incidence. [16] These data clearly establish the difference in the biologies of ALL in India from the Western world.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with both Indian and Western studies. [8161730] CNS relapse was observed in 2.4% of the patients who achieved remission. In an Indian study by Raje et al ., this figure was 1.76%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation